2016
DOI: 10.1136/postgradmedj-2016-134135
|View full text |Cite
|
Sign up to set email alerts
|

Emergency medicine educational resource use in Cape Town: modern or traditional?

Abstract: The use of modern and electronic resources is relatively common, but traditional educational resources are still preferred. This study illustrates an opportunity for greater integration of online resources and social media in educational activities to enhance multimodal and self-directed learning. Specific training in the use of these resources and how to appraise them may further improve their utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Low cost dissemination could take the form of research highlights posters in health care facilities or press releases using local newspapers and radio stations [18] . Social media can also effectively be used to sign post content or to disseminate research highlights [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Low cost dissemination could take the form of research highlights posters in health care facilities or press releases using local newspapers and radio stations [18] . Social media can also effectively be used to sign post content or to disseminate research highlights [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Although peer-review is by no means a perfect process, and is prone to bias, the lack of it in regulating information on social media means that the reliability of such information is uncertain. 4 It is likely that students are aware of the possible shortcomings of user generated content. Despite this, the use of social media for the purposes of education continues to grow, with some reports suggesting up to 52% of health profession students use online media as their primary source of information.…”
Section: Distributive Educationmentioning
confidence: 99%
“…Currently, there is limited data on the use and benefits of educational podcasts in Southern Africa. After surveying the use of online-educational multimedia in the division of Emergency Medicine in Cape Town (EMCT), Kleynhans et al [ 14 ] reported that only 21% used educational podcasts, despite >50% accessing some form of online educational resource at least once a month.…”
Section: Introductionmentioning
confidence: 99%